Training for clerks of works / Aminah Noh - Noh, Aminah (1988)
Advancement in technology in construction industry is progressing rapidly, where men's expertise has allowed the introduction of various materials and methods of construction. Unlike decades ago building clients are more sophisticated and demand good quality work. On his behalf, a competent person known as Clerk of Works is appointed for the purpose of close inspection, for better quality control. This will help him obtain better value for his investment and to reduce complications at a later date when the job is completed. An effective inspection and supervision would greatly reduce delays and disagreements which in Turn save in time, money and reputations of all parties concerned,